Integrating palliative care into neurology services: what do the professionals say?. Issue 1 (3rd August 2017) - Hepgul, Nilay; Gao, Wei; Evans, Catherine J; Jackson, Diana; van Vliet, Liesbeth M; Byrne, Anthony; Crosby, Vincent; Groves, Karen E; Lindsay, Fiona; Higginson, Irene J
Abstract : Objectives: Evaluations of new services for palliative care in non-cancer conditions are few. OPTCARE Neuro is a multicentre trial evaluating the effectiveness of short-term integrated palliative care (SIPC) for progressive long-term neurological conditions. Here, we present survey results describing the current levels of collaboration between neurology and palliative care services and exploring the views of professionals towards the new SIPC service. Methods: Neurology and palliative care teams from six UK trial sites (London, Nottingham, Liverpool, Cardiff, Brighton and Chertsey) were approached via email to complete an online survey. The survey was launched in July 2015 and consisted of multiple choice or open comment questions with responses collected using online forms. Results: 33 neurology and 26 palliative care professionals responded. Collaborations between the two specialties were reported as being 'good/excellent' by 36% of neurology and by 58% of palliative care professionals. However, nearly half (45%) of neurology compared with only 12% of palliative care professionals rated current levels as being 'poor/none'. Both professional groups felt that the new SIPC service would influence future collaborations for the better. However, they identified a number of barriers for the new SIPC service such as resources and clinician awareness. Conclusions: Our results demonstrate the opportunity to increase collaboration between neurology and palliative care services for people with progressive neurological conditions, and the acceptability of SIPC as a model to support this. Trial registration number: ISRCTN18337380; Pre-results.